Thyroid dysfunction in children and adolescents affected by undernourished and overnourished eating disorders - Calcaterra, Valeria; Magenes, Vittoria Carlotta; Siccardo, Francesca; Hruby, Chiara; Basso, Martina; Conte, Veronica; Maggioni, Giulia; Fabiano, Valentina; Russo, Susanna; Veggiotti, Pierangelo; Zuccotti, Gianvincenzo (Frontiers in Nutrition, 2023)
Eating disorders (ED) are one of the most prevalent chronic disorders in adolescents and young adults with a significant growing prevalence in younger children, particularly in females. Even if obesity per se is not framed as an eating disorder and it has always been considered a separate pathology, ED and obesity could be considered as part of a continuum: it has become evident how one condition can lead to the other, such as binge eating disorder and bulimia nervosa and that they share the same repercussions in term of psychosocial, metabolic and nutritional health The aim of this narrative review is to investigate the hypothalamic-pituitary-thyroid axis in under and over-nourished ED patients including obesity, in order to resume the relationship between control weight and thyroid function and its effects and to consider therapeutic and preventive strategies in children and adolescents. Literature data report that thyroid alterations occur in ED patients, both underweight and over-weight status and represent a continuum of changes depending on the severity and time course of the disease involving endocrine system. Considering the relevant role of thyroid hormones (TH) play a crucial role on EE, but also on the metabolic control and cardiovascular risk related to dysmetabolism and mood regulation, a continuous monitoring of thyroid homeostasis in patient with ED is mandatory to prevent severe complications and to start an early treatment when necessary.